Sons de Salles e Santiago: análise dos elementos sonoros de Santiago reflexões sobre o material bruto - Leão, Daniel Velasco (2013)
This dissertation examines how the sound elements are prepared and used in Santiago, a movie documentary directed by João Moreira Salles, to build an essay self-reflective and a melodramatic narrative, adressing the fundamental issues of the theoretical study of this form of making movies (Jean-Louis Comolli, Guy Gauthier and Bill Nichols) and the study of the cinematic sound (most notably from Michel Chion), in addition to maintaining a critical dialogue with the numbered reviews the film deserved when released